(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: Both honeybees (Apis spp.) and stingless bees (Trigona spp.) produce honeys which normally taken orally, have high nutritional and therapeutics value. Until recently, phytochemical comparison of both honey is still scarce and elucidating cytotoxicity effects on human gingival fibroblast cells (HGF) in oral cavity is of interest. Materials and Methods: Kelulut honey (KH), acquired from the stingless bees and acacia honey (AH) from the sting bees honey samples were underwent GC-MS analysis to ascertain their composition. HGF were exposed to various concentrations of KH and AH from the lowest 0.015% to the highest 5% by MTT assay for 24h, 48h and 72h. Results: GC-MS analysis determined various beneficial compounds such as flavonoids, furans, pyrans, levoglucosan and hydroxymethylfurfural from both of honey samples. MTT assay showed that the HGF cells demonstrated good viability up to percentages (v/v) as high as almost 2% in both honeys. The IC50 values for both honey for all time frames fall at above 2%. Conclusion: Both honey showed good survivability of HGF cells up to 2% of concentration. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 158-164